2008
DOI: 10.1007/s10661-008-0338-y
|View full text |Cite
|
Sign up to set email alerts
|

Airborne exposure to chemical substances in hairdresser salons

Abstract: Several studies indicate health problems among hairdressers to be related to their chemical exposure at work. The purpose of this study was to describe the exposure of chemical compounds in the air of Spanish hairdresser salons, and to study differences between salons in central and suburban areas. Ten hairdresser salons were examined for two days, by recording number and type of customers, ventilation and size of salon. Both stationary and personal borne samples for organic compounds were collected, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 27 publications
5
44
0
Order By: Relevance
“…In a Canadian study, 112 of 252 products tested were found to contain at least one phthalate at a detectable level 43) . The variations of the concentrations of chemical exposures were described in several studies 37,38,44) . In general, chemical product concentrations vary according to the use of the specific products, the number and type of products that were opened during the measurements, the number of treatments performed, and workplace ventilation 37,44) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Canadian study, 112 of 252 products tested were found to contain at least one phthalate at a detectable level 43) . The variations of the concentrations of chemical exposures were described in several studies 37,38,44) . In general, chemical product concentrations vary according to the use of the specific products, the number and type of products that were opened during the measurements, the number of treatments performed, and workplace ventilation 37,44) .…”
Section: Discussionmentioning
confidence: 99%
“…2−5) . Both dermal absorption and inhalation are relevant exposure routes for hairdressers and cosmetologists 6,7) . It is also noteworthy that these occupations involve physical exertion, long periods of standing and walking in the workplace, awkward postures, and psychosocial factors that can potentially interfere with reproduction 8−10) .…”
mentioning
confidence: 99%
“…Hairdressing is also known as a high-risk occupation because of problems such noise, higher temperature, electrical appliances and contact with cosmetic products like shampoo, creams, dyes and conditioners that contain many chemicals. These chemical substances with allergen and irritant effects cause health problems such as respiratory, skin and ocular diseases in hairdressers (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…These hair products contain a variety of chemical agents that hairdressers may be exposed to on a continuous daily basis (2,3). Even though concentrations of single chemicals generally are considered to be low in hairdresser salons (4), the long-term consequences of exposure to the complex chemical mixture are unknown.…”
mentioning
confidence: 99%
“…These compounds include hexane, benzene, toluene and metoxypropanol and endocrine-disruptive chemicals (EDC) (eg, alkylphenolic compounds and phthalates) (4)(5)(6). EDC exposures have shown associations with the genital diseases cryptorchidism (incomplete testicular descent) and hypospadias (displacement of the urethral opening along the ventral shaft of the penis) (7,8).…”
mentioning
confidence: 99%